2017
DOI: 10.11613/bm.2017.022
|View full text |Cite
|
Sign up to set email alerts
|

Policies and practices in haemostasis testing among laboratories in Croatia: a survey on behalf of a Working Group for Laboratory Coagulation of the Croatian Society of Medical Biochemistry and Laboratory Medicine

Abstract: IntroductionThe objective of this survey was to assess current policies and practice in haemostasis testing among both hospital and outpatient laboratories in Republic of Croatia.Materials and methodsA questionnaire with seventy questions divided into nine sections was created in May 2015. Participants were asked about their practice related to test request form, sample collection, prothrombin time (PT) and activated partial thromboplastin time assays, other individual haemostasis assays, point-of-care testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Recommendations on procedures in preanalytical, analytical and postanalytical phases of coagulation screening assays PT, aPTT, TT, fibrinogen, and D-dimer testing were created by the Working Group for Laboratory Coagulation (WGLC) formed by the Croatian Society of Medical Biochemistry and Laboratory Medicine (CSMBLM). Creation of the recommendations was prompted by the results obtained in the survey carried out by WGLC in 2015 among Croatian medical biochemistry and transfusion laboratories performing coagulation testing ( 6 ). Data provided in this review were collected by searching the PubMed and Ovid databases, as well as relevant publications of the Clinical & Laboratory Standards Institute (CLSI), British Society for Haematology (BSH) and International Society on Thrombosis and Haemostasis (ISTH).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recommendations on procedures in preanalytical, analytical and postanalytical phases of coagulation screening assays PT, aPTT, TT, fibrinogen, and D-dimer testing were created by the Working Group for Laboratory Coagulation (WGLC) formed by the Croatian Society of Medical Biochemistry and Laboratory Medicine (CSMBLM). Creation of the recommendations was prompted by the results obtained in the survey carried out by WGLC in 2015 among Croatian medical biochemistry and transfusion laboratories performing coagulation testing ( 6 ). Data provided in this review were collected by searching the PubMed and Ovid databases, as well as relevant publications of the Clinical & Laboratory Standards Institute (CLSI), British Society for Haematology (BSH) and International Society on Thrombosis and Haemostasis (ISTH).…”
Section: Methodsmentioning
confidence: 99%
“…The recent survey conducted among diagnostic laboratories performing coagulation testing, showed that one of the main problem is related to the lack of information on the test request ( 6 ). Lack of appropriate information such as suspected diagnosis or anticoagulation therapy can lead to misinterpretation of test results as well as to unnecessary testing or retesting which could result in additional costs.…”
Section: Preanalytical Phase In Coagulation Testingmentioning
confidence: 99%
See 3 more Smart Citations